Comparison of Postoperative Opioid Consumption Following Hallux Valgus Correction Procedures. Issue 4 (16th October 2019) - Rogero, Ryan; Fuchs, Daniel; Nicholson, Kristen; Shakked, Rachel J.; Winters, Brian S.; Pedowitz, David I.; Raikin, Steven M.; Daniel, Joseph N.
Category: Bunion Introduction/Purpose: Postoperative pain management following orthopaedic surgeries is challenging, and the opioid epidemic has made it essential to better individualize opioid prescriptions by patient and procedure. Previous studies have looked at modifications to intraoperative protocols to reduce postoperative pain and opioid analgesia following hallux valgus (HV) surgery, but to our knowledge, no previous study has compared HV procedure types in terms of postoperative narcotic consumption. The purpose of this subgroup analysis of a prospective study was to compare postoperative opioid pill consumption between 4 common HV correction procedures and to identify any patient factors associated with consumption levels. Methods: Patients undergoing outpatient HV correction procedures with 5 fellowship-trained foot & ankle surgeons over a 1- year period were included. Patients were excluded if they were <18 years of age, prescribed chronic opioid analgesics prior to date of surgery, or if they underwent concomitant non-forefoot procedures. The type of opioid prescribed and the number of opioid pills dispensed were recorded. At the first postoperative visit, the patient was asked how many prescribed opioid pills were consumed. Number of consumed pills was confirmed by a member of the research team. Opioid pills were standardized to morphine equivalent units (MEUs) and back-converted to an equivalent number of 5 mg oxycodone pills. Linear regression analysis was performed to determine if any of the 4 procedure categories, with or without concomitant lesser toe procedures, preoperative Visual Analog Scale (VAS) for pain, or patient factors (age, sex, BMI, smoking, comorbidities) were independently associated with postoperative opioid consumption. Results: One-hundred thirty-seven patients (86% female) were included in the study, with a mean age of 53.1 years and mean BMI of 26.7 kg/m2. 53% of patients received single-shot nerve blocks and 34% continuous nerve catheters. Overall, patients were prescribed a median 50 pills and consumed a median 27 pills. Thirty-six patients (26%) underwent primary chevron osteotomies, 78 (56%) underwent primary proximal osteotomies (Ludloff, scarf), 10 (7%) underwent soft tissue-only procedures and/or proximal phalanx osteotomies (modified McBride, Akin), and 13 (9%) underwent 1st MTP arthrodeses. There was no significant difference in opioid intake between the 4 procedures, including when subdivided into those with and without lesser toe procedures. Higher preoperative VAS pain score (p=.028) and younger age (p=.042) were associated with higher opioid pill consumption. Conclusion: Our study has demonstrated a lack of difference between hallux valgus procedures in terms of postoperative opioid consumption, which is important for surgeons to recognize when prescribing for a commonly performed forefoot surgery. Patients reporting higher pain levels prior to surgery were more likely to take greater postoperative pain medication. Additionally, in accordance with previous results in foot and ankle surgery, younger patient age is associated with higher postoperative opioid consumption. In light of our results, we cannot recommend differential opioid prescribing based on the specific type of hallux valgus procedure performed.